Palatal pedicle graft for management of a severe case of black triangle: A case report - Saket Kashyap; Siddharth Rai; Sandeep JN; Sushama R Galgali (International Journal of Oral and Craniofacial Science - Peertechz Publications, 2019)
Development of black triangles following surgical periodontal therapy in severe cases of periodontitis is a common complication faced by patients and clinicians. Restoring the natural form of the interdental area is of utmost importance especially when the anterior aesthetic zone is involved. A wide variety of approaches have been advocated to manage such aesthetic endeavours, which range from soft tissue manipulation to masking with restorative materials. However, the management of black triangles, particularly in cases of treated severe periodontal disease, requires a multidisciplinary approach to recreate the papillary anatomy. This presentation is a case report on management of a case with severe papillary recession occurring after flap surgery. The patient was treated with a combined approach with papilla reconstruction surgery using Coronally Advanced Flap (CAF) and Palatal Pedicle Rotation (PPR) graft and direct composite build-up.